2016
DOI: 10.1021/acs.jpcb.6b08601
|View full text |Cite
|
Sign up to set email alerts
|

Structural Response of Human Serum Albumin to Oxidation: Biological Buffer to Local Formation of Hypochlorite

Abstract: The most abundant plasma protein, human serum albumin (HSA), plays a key part in the body's antioxidant defense against reactive species. This study was aimed at correlating oxidant-induced chemical and structural effects on HSA. Despite the chemical modification induced by the oxidant hypochlorite, the native shape is preserved up to oxidant/HSA molar ratio <80, above which a structural transition occurs in the critical range 80-120. This conformational variation involves the drifting of one of the end-domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Thus, it has an important role in fighting bacteria and spurring inflammation. Nonetheless, HOCl is readily detoxified by cellular thiols 77 , albumin 78 , and cross linking of biological molecules via non-disulfide bonds 79 , effectively limiting its damage to host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has an important role in fighting bacteria and spurring inflammation. Nonetheless, HOCl is readily detoxified by cellular thiols 77 , albumin 78 , and cross linking of biological molecules via non-disulfide bonds 79 , effectively limiting its damage to host cells.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,56 Finally it must be considered that the SEC separation able to provide cleaner monodisperse samples and not used in our experiments could represent a crucial issue in the elucidation of such small details in the albumin unfolding and explain the inconsistency. However, to our experience the application or not of a SEC separation seemed not to significantly affect the observation of conformational transitions in albumin samples, 25 as also demonstrated by the agreement between the scattering profiles and models of the acid isomers obtained from our approach and those suggested on the basis of SEC-SAXS experiments. 20 Acid Unfolding of HSA Binding Palmitic Acid.…”
Section: ■ Resultsmentioning
confidence: 99%
“…13 Overall, the design of experiment with controlled parameters and relevant characterization is not trivial. Therefore, in this study, we applied a simultaneous SAXS and fluorescence characterization performed with the SUrF platform 24,25 to follow the controlled acidification of a solution of HSA in time. The high sampling rate over the pH interval helped clarify the multistep nature of the acid transition of serum albumin and identify the scattering profiles of characteristic conformers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This not reversible process (HNA-2) of albumin oxidation may be associated with an increased mortality and morbidity during sepsis, whereas a reduced average serum albumin may oppose the solution of primary infection. [32] The Italian Multicenter Study "Albios" 33 confirmed the central role of albumin levels in sepsis and infectious disease pathologies. [33] In the end we are sure that albumin normal level is on of the principal driven of sepsis treatment.…”
Section: Albumin and Sepsismentioning
confidence: 98%